RELOCATION: ESSENCE, TYPES AND PROBLEMS - ZAPUKHLIAK, Ivanna; KRASNIAK, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the concept of "relocation" and classifies the types of relocation according to the relevant characteristics. The peculiarities of each type of relocation, in particular the movement of a person - community - employee - enterprise, have been studied in detail. Business relocation for domestic economic entities has recently been of highly relevance, and practical experience of capacity relocation is practically non-existent. However, the conditions in which we all found ourselves forced us to make quick decisions in an almost unpredictable environment: to provide displaced people with work and to "save" production facilities. The advantages of relocation for both employees and enterprises are outlined. The transfer of a person may take place in order to find a new, better job, or the transfer of individual employees to a branch, department of the company located in another place in order to improve their functioning, or within the scope of the employee’s career growth. We note that the key point in business relocation will be the relocation and adaptation of employees, while regardless of the type of relocation, it is necessary to harmonize the interests and balance the needs of the employer and the employee. For example, if possible, offer short-term business trips; flexible work schedule, or work at home - remotely to avoid long business trips; weekly trips to work with accommodation in rented premises, etc. Problems and measures to facilitate the adaptation of workers in the process of relocation are given. If employees do not wish to relocate due to family or property reasons, employers may offer the employee alternative relocation options. The peculiarities of the relocation of domestic enterprises in the conditions of war are considered.